(untitled) (Eurasian Journal of Learning and Academic Teaching, 2025)
The article examines neologisms as a phenomenon that plays an important role in the development of the modern Russian language. The classification of neologisms, their main types and functions are studied. Neologisms are new words, expressions or meanings that appear in the language in response to the needs of society, technology, culture and science. The article also highlights the ways of forming neologisms, their role in the language and their influence on the linguistic picture of the world